PENGARUH PROFITABILITAS, KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, TERHADAP NILAI PERUSAHAAN: - Ateri Dendi; Yance Sumantri; Dimas Atmalta; Trendi Tri Rahmat (Yayasan Nuraini Ibrahim Mandiri, 2024)
A company is founded with the aim of achieving maximum profits or maximum profits and optimizing company value. Company value can describe the condition and financial performance of a company. The aim of this research is to determine the influence of profitability, investment decisions, funding decisions, dividend policy and company size on company value. This type of research uses a systematic literature review By collecting literature reviews obtained from Google Scholar methodology and empirical data analysis techniques. The results of this research state that profitability has a very positive and significant influence on investment decisions, funding decisions, dividend policy and company size on company value.